Anion-Stoichiometry-Dependent Selectivity Enhancement in Ion-Paired Chiral Ligand–Palladium Complex Catalyzed Enantioselective Allylic Alkylation - Ohmatsu, Kohsuke; Hara, Yoshiyuki; Kusano, Yuya; Ooi, Takashi (Synlett, 2016)
The ratio of chiral Brønsted acid to ammonium–phosphine hybrid ligand in the in situ preparation of ion-paired chiral ligands was found to have a notable effect on the stereocontrolling ability of the corresponding palladium complex. The use of supramolecular palladium complexes generated from palladium metal, ammonium phosphine, and a chiral phosphoric acid in a ratio of 1:2:3 enabled an excellent level of enantiocontrol in the catalytic asymmetric allylation of α-nitrocarboxylates with a functionalized allylic carbonate.
Keywords: ion pair; chiral ligand; supramolecular catalyst; palladium; allylic alkylation